Livro sobre cuidados com dermatite associada à incontinência em recém-nascido, criança, adulto e idoso - Raposo, Mayara Leticia Matos De Menezes [UNIFESP] (2020)
Introduction: Incontinence-Associated Dermatitis (IAD) is an inflammation of the skin caused by its prolonged contact with urine and/or feces. It affects all age groups, especially at the extremes of age. The management of IAD is a major challenge for health professionals. Thus, it is necessary to develop an educational resource containing the most relevant information about management of IAD at all stages of life. Objective: To develop and validate a book on the management of IAD in newborns, children, adults, and older adults. Methods: A descriptive exploratory study. The chapters of the book were defined after a search for studies published since 2009 in the PubMed/Medline, LILACS, BDENF, and EMBASE databases, using the keywords: adult, child, dermatitis, diaper rash, urinary incontinence, fecal incontinence, and aged. The written content and illustrations were then created. Upon completion, the book was validated by experts through the Delphi technique and the Content Validity Index was calculated. Results: After the review of the literature, the book chapters were defined and text content was written and proofread to improve grammar and readability. The illustrations were then included and the book layout was designed. The book was validated by seven experts through two rounds of consultation, achieving a 96% level of agreement among them. Conclusion: The book on the Management of Incontinence-Associated Dermatitis in newborns, children, adults, and older adults was developed and validated.